Integrating 3D survey and open datasets for creating low-cost urban digital twins in VR - Y. Lei; N. Bruno; R. Roncella (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences)
This paper presents a low-cost framework for creating urban digital twins in Virtual Reality (VR) tailored for heritage preservation and smart city applications. The increasing demand for urban digital twins necessitates an integration of diverse data sources to enhance urban management, particularly in historical contexts where traditional methods may lack necessary specificity. To address this, our research integrates advanced 3D survey techniques (mostly low-cost) with publicly available datasets to develop a semantically rich, detailed urban digital model aligned with specific requirements of each unique urban setting. The methodology hinges on three pivotal stages: data acquisition, data management, and data accessibility. Data acquisition involves collecting extensive data both from existing datasets and 3D surveys, emphasizing on identifying optimal, cost-effective solutions suited to the surveyed area. Data management is achieved using a broker database coupled with a Web Application Programming Interface (Web API), ensuring the integrity of original databases while enabling flexible system implementation. Data accessibility extends to a broad range of applications, including GIS, BIM, and customized applications, enhancing the scalability of the digital twin model. The test ground of this system is a VR application developed with Unity, which serves as the interactive platform for the digital twin model. The proposed framework is validated through three case studies in distinct urban settings, each chosen to illustrate the framework's adaptability, versatility, and effectiveness in different urban complexities. The results demonstrate the potential of the digital twin model in facilitating detailed urban management tasks, promoting sustainable heritage conservation, and fostering smarter urban environments.